Rock salt and boron supplementation: Effects on oxidative stress in blood and semen of rams - Akarsu, S; Şimşek, ÜG; Erişir, M; Sönmez, M; Güngör, İH and Acisu, TC and Erdem, M and Şimşek, MA and Elçi, EN (Journal of the Hellenic Veterinary Medical Society, 2025)
This study aimed to investigate the effects of boron and rock salt minerals, which are interesting as antioxidant minerals on malondialdehyde (MDA) and some antioxidants; glutathione level (GSH), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT) enzyme activities in blood and sperm cells. For this purpose, a total of 36 rams were divided into six research groups, with six rams in each group. The research groups were designed as Control (Just 40 ml water), Salt (10 g rock salt/day), B20 (20 mg boric acid/day), B40 (40 mg boric acid/day), BT20 (20 mg boric acid + 10 g rock salt/day), BT40 (20 mg boric acid + 10 g rock salt/day). The additives were dissolved in 40 ml of water and administered orally with 50 ml syringes for 80 days. Semen and blood samples were taken from the rams at the end of the experiment. Salt added to the diet significantly increased MDA levels in blood and sperm cells. A significant decrease in plasma MDA levels were observed in the BT40 group and sperm cells in the B40 and BT40 groups. Salt and boric acid were found to be effective on GSH and antioxidant enzymes. In conclusion, it was found that boric acid added to the diet at a dose of 40 mg enhanced antioxidant metabolism and significantly reduced salt-induced lipid peroxidation.